Potential molecular mechanism of exercise reversing insulin resistance and improving neurodegenerative diseases - Shen, Jiawen; Wang, Xianping; Wang, Minghui; Zhang, Hu (Frontiers in Physiology, 2024)
Neurodegenerative diseases are debilitating nervous system disorders attributed to various conditions such as body aging, gene mutations, genetic factors, and immune system disorders. Prominent neurodegenerative diseases include Alzheimer's disease, Parkinson's disease, Huntington's disease, amyotrophic lateral sclerosis, and multiple sclerosis. Insulin resistance refers to the inability of the peripheral and central tissues of the body to respond to insulin and effectively regulate blood sugar levels. Insulin resistance has been observed in various neurodegenerative diseases and has been suggested to induce the occurrence, development, and exacerbation of neurodegenerative diseases. Furthermore, an increasing number of studies have suggested that reversing insulin resistance may be a critical intervention for the treatment of neurodegenerative diseases. Among the numerous measures available to improve insulin sensitivity, exercise is a widely accepted strategy due to its convenience, affordability, and significant impact on increasing insulin sensitivity. This review examines the association between neurodegenerative diseases and insulin resistance and highlights the molecular mechanisms by which exercise can reverse insulin resistance under these conditions. The focus was on regulating insulin resistance through exercise and providing practical ideas and suggestions for future research focused on exercise-induced insulin sensitivity in the context of neurodegenerative diseases.